The Effect of Storage Time and Different Anticoagulants on Fasting Blood Glucose Concentration - Al Salhen, Khaled S.; Saad , Eman K.; Aznine, Aml J. (Al-Mukhtar Journal of Sciences, 2018)
The comparative stabilizing effects of storage time and the anticoagulants; fluoride oxalate, EDTA, sodium citrate, and serum on ice slurry; on fasting blood glucose level were determined using the spectrophotometry method. Fasting blood samples were taken from 75 non-diabetic male people, and the blood glucose levels determined at 30 min intervals for a maximum time of 3 hours. Our results showed that the rate at which plasma glucose changes with time varies with specific anticoagulants. From the results, it was observed that the rate at which the blood glucose decreases with time vary with specific anticoagulants. It was noticed that random blood glucose in sodium citrate, EDTA, fluoride oxalate and serum on ice slurry decreased at a mean value of 28.4mg/dl, 58mg/dl, 15.4mg/dl and 60.2mg/dl dl after 3 hours respectively. With respect to the concentration of glucose before storage, this suggests that storage of blood using fluoride oxalate as an anticoagulant tends to better preserve the glucose level over a long period of time. Transport on ice slurry and rapid separation of serum within 30 min can inhibit glycolysis without the addition any anticoagulants (% reduction 1.3). Thus, from our findings, it is obvious that irrespective of the specimen type, time of collection or type of anticoagulant, the concentration of blood glucose remained unstable during storage. It is therefore suggested that analysis of blood glucose should be carried out immediately after collection of specimen or within the shortest possible time after storage in an anticoagulant to obtain a reliable result.